Invasion and metastasis in pancreatic cancer - Büchler Markus W (Molecular Cancer, 2003)
Abstract Pancreatic cancer remains a challenging disease with an overall cumulative 5-year survival rate below 1%. The process of cancer initiation, progression and metastasis is still not understood well. Invasion and tumor metastasis are closely related and both occur within a tumour-host microecology, where stroma and tumour cells exchange enzymes and cytokines that modify the local extracellular matrix, stimulate cell migration, and promote cell proliferation and tumor cell survival. During the last decade considerable progress has been made in understanding genetic alterations of genes involved in local and systemic tumor growth. The most important changes occur in genes which regulate cell cycle progression, extracellular matrix homeostasis and cell migration. Furthermore, there is growing evidence that epigenetic factors including angiogenesis and lymphangiogenesis may participate in the formation of tumor metastasis. In this review we highlight the most important genetic alterations involved in tumor invasion and metastasis and further outline the role of tumor angiogenesis and lymphangiogenesis in systemic tumor dissemination.